THE ROLE OF VISUAL ART IN FACING THE CORONA PANDEMIC - Duaa Mohammed Alashari (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2022)
Art is constantly inspired by what happens in its social and cultural context. The arts cannot be separated from life and the significant events in the world, whether it is a war, a natural disaster, or the spread of a disease an epidemic. Today, the whole world is witnessing the Coronavirus (Covid-19) pandemic, one of the worst in human history. The current scene has taken hold of artwork and the visual arts. The spread of the virus has inspired many artists to produce paintings, posters and artwork. This study aims to reveal the role and importance of Arab artists regarding the message they present regarding the situation at hand. In this study, the qualitative data was amassed as part of the methodology. The qualitative descriptive method and the case study approach are the primary approaches for the data collection. The results section focuses on the answers obtained from Arab artists through their artwork. It is held via a virtual exhibition. The discussion section focuses on a detailed analysis of the paintings. The study results concluded that art is a kind of documentation of all of the events that happen to humans. Art is a record of historical events, so it is a bright spot in times of crisis and darkness. Through these paintings, Arab artists have provided a light to those who feel gloomy in these difficult times, indicating that those in the Arab world focus on the unity of place, language and religion. Therefore, this artistic movement moves between all its countries so that no matter how harsh the situation, people will remain unified.